PEMBELAJARAN KREATIF BERBASIS LITERASI BAHASA MENUMBUHKAN ANAK YANG CERDAS DAN KREATIF - Umi Khomsiyatun (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: This article discusses the scientific creative learning process based on language literacy. The purpose of this article is to describe how scientific-based creative learning based on language literacy can develop intelligent and creative children so that they can be in the world. Creative learning is a dynamic, fun, and creative learning so that children are directly involved through fun activities in learning. Creative learning based on language literacy can stimulate children's motivation. Implementation of creative learning based on language literacy can be done on the process of observing, asking, trying, reasoning and communicating during the learning process takes place. Keywords: Pembelajaran Kreatif, Saintifik, dan Literasi Bahasa.